Acquired neuromyotonia in thymoma‐associated myasthenia gravis: a clinical and serological study. (25th March 2019) - Gastaldi, M.; De Rosa, A.; Maestri, M.; Zardini, E.; Scaranzin, S.; Guida, M.; Borrelli, P.; Ferraro, O. E.; Lampasona, V.; Furlan, R.; Irani, S. R.; Waters, P.; et al.
Abstract : Background and purpose: Acquired neuromyotonia can occur in patients with thymoma, alone or in association with myasthenia gravis (MG), but the clinical prognostic significance of such comorbidity is largely unknown. The clinico‐pathological features were investigated along with the occurrence of neuromyotonia as predictors of tumour recurrence in patients with thymoma‐associated myasthenia. Methods: A total number of 268 patients with thymomatous MG were studied retrospectively. Patients with symptoms of spontaneous muscle overactivity were selected for autoantibody testing using immunohistology for neuronal cell‐surface proteins and cell‐based assays for contactin‐associated protein 2 (CASPR2), leucine‐rich glioma inactivated 1 (LGI1), glycine receptor and Netrin‐1 receptor antibodies. Neuromyotonia was diagnosed according to the presence of typical electromyography abnormalities and/or autoantibodies against LGI1/CASPR2. Results: Overall, 33/268 (12%) MG patients had a thymoma recurrence. Five/268 (2%) had neuromyotonia, four with typical autoantibodies, including LGI1 ( n  = 1), CASPR2 ( n  = 1) or both ( n  = 2). Three patients had Netrin‐1 receptor antibodies, two with neuromyotonia and concomitant CASPR2+LGI1 antibodies and one with spontaneous muscle overactivity without electromyography evidence of neuromyotonia. Thymoma recurrence was more frequent in those with (4/5, 80%) than in those without (28/263, 10%, P  < 0.001) neuromyotonia. Neuromyotonia preceded the recurrence in 4/5 patients. In univariate analysis, predictors of thymoma recurrence were age at thymectomy [odds ratio (OR) 0.95, 95% confidence interval (CI) 0.93–0.97], Masaoka stage ≥IIb (OR 10.73, 95% CI 2.38–48.36) and neuromyotonia (OR 41.78, 95% CI 4.71–370.58). Conclusions: De novo occurrence of neuromyotonia in MG patients with previous thymomas is a rare event and may herald tumour recurrence. Neuronal autoantibodies can be helpful to assess the diagnosis. These observations provide pragmatic risk stratification for tumour vigilance in patients with thymomatous MG.